Challenges of Online Modules for Task-Based Learning of Mathematics for Effective Online Teaching-Learning Process - Upadhyay, Poonam; Mohammed, Lubna Ali (International Journal of Emerging Issues in Social Science, Arts and Humanities ( IJEISSAH), 2022)
The COVID-19 pandemic caused a sudden shut down of educational institutions, which resulted in learning challenges among the students as the education medium switched to online mode. Mathematics learning based on online modules tasks is challenging for the students due to its complexity. Therefore, this study aims to elaborate challenges of online modules for task-based mathematics learning for an effective online teaching-learning process. In particular, this study explores the challenges involved in online mathematical education, the concepts of task-based learning for online mathematics modules and determined task-based learning of mathematics for an effective online teaching-learning process. Using a literature review methodology and content analysis approach to analyze the research papers, 33 recent articles (i.e., from 2020 to 2021) were selected with a focus to COVID-19 for analysis and extract data for the analysis. The research has proposed a conceptual framework that can guide researchers to explore and explain online modules' challenges for task-based mathematics learning for effective online teaching and learning processes.